2022
DOI: 10.3389/feart.2022.880462
|View full text |Cite
|
Sign up to set email alerts
|

Subseasonal to Annual Long-Term Trends in Climate Extremes Over East Asia, 1981–2021

Abstract: This study examines the up-to-date observed trends of subseasonal to annual range climate extremes over the East Asia region using the high-resolution global unified gauge-based analysis of the NOAA Climate Prediction Center for 1981–2021. The spatial extent of extreme events is identified using the Expert Team on Climate Change Detection and Indices (ETCCDI)-based modified climate extreme index (EmCEI) with five subcomponents (maximum temperature, minimum temperature. total rainfall, heavy rainfall, and wet a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 40 publications
1
1
0
Order By: Relevance
“…The analysis of the extreme climate index indicated that extreme temperature has generally increased in mainland China, while extreme precipitation has not changed significantly over the years, as depicted in Figure 5. This outcome supports the findings of other research studies [8,42,43]. Comparable patterns have been found in various regions of China, such as the agro-pastoral zone in North China [13], eastern coastal area [44], the Yangtze River Basin [45], and the Qinghai-Tibet Plateau region [46].…”
Section: Dynamic Of Nep and Extreme Climate Indices In Mainland Chinasupporting
confidence: 90%
“…The analysis of the extreme climate index indicated that extreme temperature has generally increased in mainland China, while extreme precipitation has not changed significantly over the years, as depicted in Figure 5. This outcome supports the findings of other research studies [8,42,43]. Comparable patterns have been found in various regions of China, such as the agro-pastoral zone in North China [13], eastern coastal area [44], the Yangtze River Basin [45], and the Qinghai-Tibet Plateau region [46].…”
Section: Dynamic Of Nep and Extreme Climate Indices In Mainland Chinasupporting
confidence: 90%
“…Similarly, East Asia also experienced a rise in the frequency of such extreme climate events in recent decades 5 . Moon et al 6 reported that summer extreme heat and precipitation in East Asia increased by 4–8% over the past three decades. This increase has led to more frequent occurrences of extreme precipitation, culminating in events such as the 2018 Japan flood-heat wave succession 7 .…”
Section: Introductionmentioning
confidence: 99%